Two silly trolls - Jewell, Nancy (Ohio : Harper Collins, 1992)
Nip and Tuck, two troll brothers, share silly experiences, including building a house without a roof, getting lost on the way to their own picnic, and sharing a travelling itch.
Keywords: Trolls - fiction; Brothers-fiction.